International Roughness Index (IRI) Assessment Based on The Application of ROADBUMP and ROADROID on Sei Duri-Mempawah Road Section - Januarsih, Hafizah; Kadarini, S. Nurlaily; Mukti, Elsa Tri (Jurnal Teknik Sipil, 2024)
The research assessed the condition of the Sei Duri-Mempawah road segment using the International Roughness Index (IRI) to determine surface roughness. Two smartphone applications, Roadbump and Roadroid, were evaluated against traditional laser profilometers to measure IRI values. The results indicate that at a speed of 20 km/h, the Roadbump application showed that 26% of the left lane was in good condition, with moderate, slightly damaged, and severely damaged segments accounting for 68%, 4%, and 2%, respectively. For Roadroid at the same speed, the left lane's condition was 76% good, while moderate, slightly damaged, and severely damaged conditions were at 16%, 3%, and 5%. Both applications demonstrated variations in IRI values at higher speeds, with Roadroid generally yielding higher roughness levels than Roadbump. Comparative analysis revealed that Roadbump at 40 km/h provided results closer to the laser profilometer, with up to 78% similarity on the left lane. However, the correlation analysis with BPJN data revealed weak correlations for most cases, except for a stronger relationship (R = 0.5521) between the 40 km/h Roadbump application and the laser profilometer. Thus, Roadbump at 40 km/h is recommended for practical field assessments.